2016
DOI: 10.1038/srep28028
|View full text |Cite
|
Sign up to set email alerts
|

Venlafaxine treatment reduces the deficit of executive control of attention in patients with major depressive disorder

Abstract: Attention plays an essential role in supporting other cognitive functions and behavior, and disturbance of attention is one of the most common symptoms in major depressive disorder (MDD). Although treatment with venlafaxine for MDD symptoms has been shown to reduce deficits in cognition and emotion regulation, it remains unclear whether venlafaxine improves specific attentional functions. We used the Attention Network Test to measure the attentional functions of alerting, orienting, and executive control befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 63 publications
4
16
0
Order By: Relevance
“…Among cognitive deficits in depression, attention impairment was more particularly assessed. Indeed, attention is often considered as playing an important role in supporting other cognitive functions and behavior (Tian, 2016) and recent findings provide support for a primary attention deficit in depression (Nilsson, 2016) that might constitute a vulnerability marker for MDD (Weiland-Fiedler, 2004). The identification of an index of the attention process (the F1 marker of the d2 attention test) that has time stability and is predictive of functional recovery is consistent with these findings.…”
Section: Discussionsupporting
confidence: 55%
“…Among cognitive deficits in depression, attention impairment was more particularly assessed. Indeed, attention is often considered as playing an important role in supporting other cognitive functions and behavior (Tian, 2016) and recent findings provide support for a primary attention deficit in depression (Nilsson, 2016) that might constitute a vulnerability marker for MDD (Weiland-Fiedler, 2004). The identification of an index of the attention process (the F1 marker of the d2 attention test) that has time stability and is predictive of functional recovery is consistent with these findings.…”
Section: Discussionsupporting
confidence: 55%
“…Directly comparing with nortriptyline 1mg/lkg, Culang-Reinleib et al, 2012 reported that sertraline patients showe d significant improvement in verbal learning, and more so than nortriptyline patients, who showed no improvements (Culang-Reinlieb et al, 2012). Sertraline also improved memory in non-responders, indicating that effects on cognition may be independent of those on depression symptomatology, consistent with previous suggestions by Tian et al, 2016. Given the small sample size N=33and lack of placebo control, further replication studies are warranted.…”
Section: Act Ive Comparat or Trials Of T Radit Ional Ant Idepressant mentioning
confidence: 70%
“…This positive effect may be a direct result of serotonin and noradrenaline reuptake inhibition, improving symptomatology and cognition, although the small sample size of 81 is limiting. Interestingly, Tian et al, 2016 reported that executive control and depression symptom improvement were not correlated, indicating that these effects may potentially occur via different mechanisms.…”
Section: Placebo Cont Rolled T Rials Of T Radit Ional Ant Idepressantmentioning
confidence: 99%
See 2 more Smart Citations